Development of flexural structure for chatter machining testing - Mohamad Alif, Mohd Nasir (2012)
This thesis deals with development of flexural structure that be used in detecting chatter on milling machine. The main important point in HSM is to increase MRR thus can reduce cost and increasing production. In this problem, chatter will limit the machining process and sometime will result in damage on cutting tool and surface roughness of material. The role of SDOF flexure is used as platform to perform stability test. It will provide a flexible workpiece with natural frequency. This project is carried out to develop a flexure with ability to be adjustable in height with natural frequency 400-600Hz. The process began using analytical method to identify the natural frequency. The simple calculation was carried out by determining the stiffness of the material. From the analytical method, at height of 13 cm the natural frequency was 424.82 Hz and 580.16 Hz at height of 11 cm. In this project, mild steel was used due to strength and toughness. After the calculation was done, the flexure was modeled using solidwork software and exported to Algor software for FEA. The analysis of flexure was done in order to verify the calculation before the flexure can be fabricated. From the result of FEA, at height of 13 cm the natural frequency reading is 415.23 Hz and 495.22 Hz at height of 11 cm. The flexure that fabricated fully then will enter the final stage to test with modal analysis. The frequency response of the flexure is determined by using impact hammer with giving force at load point and been measured by the accelerometer. The result shows at height 13 cm the natural frequency was 412.5 Hz and 561.5 Hz at height of 11 cm.